Identifying requirements for airborne-supplied city hubs. (March 2023) - Roesing, J.; Lima, I.; Feldhoff, E.; Hoenen, S.; Kuehnel, F.; Theissen, A.
Abstract: As a result of the globalization, express cargo volume is rising every year. On the one hand, time-critical and highly valuable goods need to be delivered as quickly as possible. On the other hand, cities are facing multiple problems regarding their transportation system, such as increasing congestion on the roads, and air pollution. To serve the demand of express parcels and at the same time oppose these emerging challenges, an airborne "green" supply chain with low-emission vehicles can be a solution. This paper outlines the conceptual requirements of an airborne-supplied city hub that are related to urban integration, road traffic access and flight operations. First, we identified existing city hub and drone concepts in the literature. The findings were organized into a process chain. A concept for an airborne-supplied city hub was developed where the city hub serves as a transshipment center in the supply chain. For this specific research framework and the legal situation in Germany, we examined a list of mandatory and favorable requirements that may serve as a guideline for developers and providers of this new type of airborne express cargo services. Highlights: The concept for airborne-supplied city hubs is derived from ground-based supplied city hubs. It is recommended to set up the city hub as a "white label" solution. The development of each city hub depends on the integration into the according supply chain. To date, the legal framework for drone landing pads at city hubs is based on helicopter guidelines. Airborne-supplied city hubs help improve air quality in cities by supporting electric vehicles.